Pentahelix Synergy in Post-Pandemic Tourism Recovery in Batu City - Hidayatullah, Syarif; Windhyastiti, Irany; Aristanto, Eko; Rachmawati, Ike Kusdyah; Roedjinandari, Nanny (Proceedings of International Conference of Graduate School on Sustainability, 2023)
Batu is a city that has various potentials. Geographically, Batu benefits from the mountains that surround it so that the city of Batu is the only city in East Java that has the most mountains. These natural conditions make the city of Batu has a beautiful panorama, cool air and has the potential to attract more and more tourists. A qualitative approach is used in this study, this is because with qualitative research researchers will be able to explore and describe in depth the issues that you want to raise regarding Pentahelix Synergy in Post-Pandemic Tourism Recovery in Batu City. Batu City tourism development using the pentahelix approach which usually has 5 (five) elements of approach such as: academic, government, community, business, and mass media. This research results in collaboration from all elements such as government, community (tourism activists) collaboration that must occur and has a very strategic role such as the formation of a community that can be able to coordinate thematically and specifically what elements are involved in developing tourism in the city of Batu. From the results of the study, it was found that the Batu City Tourism Promotion Board had tried optimally in carrying out its duties as an agency formed and funded by the government to help promote tourism. Cooperation between actors in the pentahelix approach in Batu City can be seen from the study, the results have not been implemented optimally considering that there is still a tendency for elements in pentahelix to work partially, besides that there is still distrust between actors.